Building a bicultural bridge - Rodriguez-Keyes, Elizabeth; Piepenbring, Julie (Smith College Studies in Social Work, 2017)
The balancing act of living between two cultures can have a significant impact on the development of adolescent Latinas living in the United States. Many adolescent Latinas, particularly second generation, live with two sets of cultural values that are often in conflict with one another. This case study illustrates the importance of understanding the impact of acculturation on the individual and the family. Issues of identity, biculturalism, and bilingualismspecifically the phenomenon of language switchingare dismantled in this case study to gain deeper insight into the unique experience that second-generation Latinas undergo when negotiating two cultural orientations. These findings are important to consider when working with the Latino population as they represent one of the largest immigrant groups and the most rapidly growing group in the United States.
Keywords: Latinas; adolescent; biculturalism; bilingual psychotherapy; cultural identity; dept.swk; language switching